2011
DOI: 10.1111/j.1365-3164.2011.00987.x
|View full text |Cite
|
Sign up to set email alerts
|

Persistent, widespread papilloma formation on the penis of a horse: a novel presentation of equine papillomavirus type 2 infection

Abstract: A 9-year-old gelding presented with approximately 100 papillomas that covered about 75% of the distal penis. Biopsy was performed, and histology showed evidence of viral cytopathic change and koilocytosis. Polymerase chain reaction using DNA extracted from biopsied tissue amplified equine papillomavirus type 2 (EcPV-2) DNA sequences. Sixteen months later, the horse was re-examined and the appearance of the papillomas was unchanged. Equine papillomavirus type 2 DNA sequences were again amplified from both biops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 12 publications
(35 reference statements)
4
32
0
1
Order By: Relevance
“…There are various indications that infection with EcPV2 plays an important role in the pathogenesis of penile cancer in the horse . The current study supports this, as 90.1% of the samples were positive against only one positive result in 12 samples from normal penile skin.…”
Section: Discussionsupporting
confidence: 82%
“…There are various indications that infection with EcPV2 plays an important role in the pathogenesis of penile cancer in the horse . The current study supports this, as 90.1% of the samples were positive against only one positive result in 12 samples from normal penile skin.…”
Section: Discussionsupporting
confidence: 82%
“…These areas were sometimes involved in our cases but less prominently. The two younger horses exhibited thousands of coalescing papillomas, which is more than other equine papilloma clinical entities …”
Section: Discussionmentioning
confidence: 92%
“…Several studies have indicated a connection between EcPV2 and clinical conditions such as genital papillomas and in situ and invasive squamous cell carcinomas . There is evidence that the viral DNA can be found in most clinical samples but only occasionally in other lesions or clinically healthy skin . While papillomavirus infections in humans have been shown to be mandatory for the development of certain lesions, an overt clinical manifestation, especially malignant transformation, is also dependent on other factors .…”
Section: Discussionmentioning
confidence: 99%